Carbon dots derived from water hyacinth and their application as a sensor for pretilachlor. Issue 6 (June 2019) - Deka, Manash Jyoti; Dutta, Parlie; Sarma, Sewaljyoti; Medhi, Okhil Kumar; Talukdar, N.C.; Chowdhury, Devasish
Abstract: Recently, carbon-based nanomaterials have been attracted much interest among the scientific community due to its extraordinary properties and applications. Mostly the fluorescent carbon nanomaterials are prepared from commercially available precursors. In this work, develop a new strategy for producing carbon nanoparticles (carbon dots) using phosphoric acid as an activating agent from water hyacinth present in Assam, India. These carbon nanoparticles show green fluorescence under UV light, and the sizes are found below 10 nm. These carbon dots are applied as a fluorescence sensor for detecting the herbicide (pretilachlor). The developed PL sensor is exclusively selective and sensitive for detection of this herbicide, and the limit of detection is found to be 2.9 μM.This sensor is also tested for real samples like soil contaminated with pretilachlor.